2012
DOI: 10.1021/jf300149m
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Aroma-Active Compounds in Jiashi Muskmelon Juice by GC-O-MS and OAV Calculation

Abstract: To identify aromatic compounds in Jiashi melon juice, gas chromatography-mass spectrometry-olfactometry (GC-MS-O) analysis was used. Odor activity values (OAVs) were also calculated on the basis of the qualitative and quantitative analysis of volatile compounds. Results showed that 42 volatiles were identified, among which 4 compounds, namely, diethyl carbonate, isophorone, 2-butoxyethyl acetate, and menthol, were identified or tentatively identified for the first time as volatiles in melon fruit. Twelve compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 30 publications
8
98
1
1
Order By: Relevance
“…Geosmin exhibited the highest average OAV of 4.54, followed by bis(2-chloroisopropyl) ether, DEDS, 2-MIB, DMDS, nonanal, benzaldehyde, decanal, pyridine, etc. A compound with an OAV over 1 is considered to be important in constituting the odor profile (Pang et al, 2012). So 2-MIB and geosmin should be the key odorants responsible for the musty odor, while DMDS, DEDS and bis(2-chloroisopropyl) should be the key odorants related to the septic odor.…”
Section: Odorant Removal In Wtpmentioning
confidence: 99%
“…Geosmin exhibited the highest average OAV of 4.54, followed by bis(2-chloroisopropyl) ether, DEDS, 2-MIB, DMDS, nonanal, benzaldehyde, decanal, pyridine, etc. A compound with an OAV over 1 is considered to be important in constituting the odor profile (Pang et al, 2012). So 2-MIB and geosmin should be the key odorants responsible for the musty odor, while DMDS, DEDS and bis(2-chloroisopropyl) should be the key odorants related to the septic odor.…”
Section: Odorant Removal In Wtpmentioning
confidence: 99%
“…Extraction of Odorant Compounds from CGJ Using Manual Solid-Phase Microextraction The odorant compounds were extracted as described by Pang et al (2012) with minor modifications. A manual solid-phase microextraction fiber (Supelco Inc., Bellefonte, PA, USA) with a 50/30-μm p o l y d i m e t h y l s i l o x a n e / d i v i n y l b e n z e n e / c a r b o x e n (PDMS/DVB/CAR) coating was used for volatile extraction after the fiber had been conditioned at 250°C for 30 min.…”
Section: Odorant Analysismentioning
confidence: 99%
“…Odorants with an OAV equal to or above one are considered to be responsible for odor, and the greater their OAV is, the more they contribute to the odor profile (Pang et al, 2012). In this study, the septic and musty odorants identified were quantified using GC × GC-TOFMS for all of the six water samples, which were used to calculate the OAVs.…”
Section: Oav Determinationmentioning
confidence: 99%